Risk factor analysis for congenital heart defects in children - Lastivka, I. V.; Pishak, V. P.; RyznychukМ. О.; KhmaraТ. V. (Regulatory Mechanisms in Biosystems, 2020)
Congenital heart defects (CHDs) are the most common malformations, occurring in almost 1.0 in 100 births. We investigated an association between risk factors and CHDs, because epidemiological studies have reported conflicting results regarding risk factors and CHDs recently. The study of CHD frequency was conducted in Chernivtsi region (Northern Bukovina) on the basis of the medical genetic center. A retrospective method of research by studying registration genetic maps was used to analyze risk factors. 91 cards of infants suffering from CHD (47 boys and 44 girls) aged 0–1 living in the territory of Northern Bukovina were selected. In order to identify risk factors, 133 cards of healthy infants (77 boys and 56 girls) were used. The analysis of risk factors revealed that the female gender of a child is a risk factor for CHD development. The analysis of the ordinal number of pregnancy revealed that the second and the third pregnancies are probable risk factors for the development of this pathology. It was found in our study that folic acid intake during the first trimester prevented CHD development (OR 2.33). The study revealed that among stressful risk factors are: unplanned pregnancy (OR 3.13); out-of-wedlock pregnancy and stress during pregnancy. Maternal CHD increased the CHD development in offspring approximately by two times. Some factors, such as a woman doing hard physical work during pregnancy, having sedentary work during pregnancy, the mother being a housewife or having an incomplete secondary education (OR 3.61), the mother’s secondary education, the father’s incomplete secondary education (OR 18.62), the father serving in the army (OR 2.15) or being a student at the time of woman’s pregnancy (OR 2.97) were significant for CHD development in the fetal stage. A young age of the father (up to 43 years) was also considered as one of the risk factors. This article is expected to provide timely information on risk factors for CHD development to a wide range of medical staff, including pediatric and adult cardiologists, pediatricians, thoracic surgeons, obstetricians, gynecologists, medical geneticists, genetic counselors and other relevant clinicians.